The monumental challenge of preservation the past in a volatile world - Cloonan, Michèle Valerie 1955- (The MIT Press, 2018)
The preservation of cultural heritage is a monumental task. The aim of this book is to explore the preservation of movable, immovable, man-made, and socially constructed heritage in an expansive way. Studies in preservation have tended to reflect particular disciplinary lines : library and archival studies, museum studies, art history, historic preservation, and other fields that focus on preservation from particular vantage points. The premise of this book is that there are broad preservation issues that can be viewed through a variety of disciplines. Law, political science, business, architecture, computer science, geography, cultural tourism and cultural heritage management, sociology, and environmental science (itself a multidisciplinary academic field) are some of the fields that address preservation-related issues. For example, international laws may be essential to recovering stolen artifacts or protecting heritage in war. Natural disasters affect heritage collections; disaster preparedness and recovery can be approached from many angles including public policy, science, and the sociology of disasters. Anthropology and history offer approaches to understanding and addressing multi-cultural issues in preservation. This book considers many ways of looking at preservation and unpacks the idea that we are what we preserve"--Provided by publisher.